The gown : [compact disc, unabridged] a novel of the royal wedding - Robson, Jennifer, 1970- (Harper Audio, 2019)
London, 1947: Besieged by the harshest winter in living memory, burdened by onerous shortages and rationing, the people of postwar Britain are enduring lives of quiet desperation despite their nation's recent victory. Among them are Ann Hughes and Miriam Dassin, embroiderers at the famed Mayfair fashion house of Norman Hartnell. Together they forge an unlikely friendship, but their nascent hopes for a brighter future are tested when they are chosen for a once-in-a-lifetime honor: taking part in the creation of Princess Elizabeth's wedding gown.